Molecular Detection of Zoonotic and Veterinary Pathogenic Bacteria in Pet Dogs and Their Parasitizing Ticks in Junggar Basin, North-Western China - Guo, Jia; Song, Shengnan; Cao, Shuzhu; Sun, Zhihua; Zhou, Qiyue; Deng, Xingmei; Zhao, Tianyi; Chai, Yingjin; Zhu, Dexin; Chen, Chuangfu; Baryshnikov, P. I.; Blair, Hugh T.; et al. (Frontiers in Veterinary Science, 2022)
Despite the recognized epidemiological importance of ticks as vectors for pathogens that cause numerous zoonotic and veterinary diseases, data regarding the pathogens of pet dogs and their parasitic ticks in the Junggar Basin are scarce. In this study, a total of 178 blood samples and 436 parasitic ticks were collected from pet dogs in Junggar Basin, Xinjiang Uygur Autonomous Region (XUAR), north-western China. All ticks were identified as Rhipicephalus turanicus sensu stricto (s.s.) according to morphological and molecular characteristics. Rh. turanicus s.s. ticks were collected from pet dogs in China for the first time. Seven tick-borne pathogens, such as Ehrlichia chaffeensis, Anaplasma phagocytophilum, Rickettsia massiliae, Candidatus R. barbariae, Brucella spp., Rickettsia sibirica, and Anaplasma ovis, were detected from ticks, whereas the first five bacteria were detected from blood samples of dogs. Brucella spp. was the most predominant pathogen in both blood samples and ticks of pet dogs, with the detection rates of 16.29 and 16.74%, respectively. Moreover, 17 ticks and 1 blood sample were co-infected with two pathogens, and 1 tick was co-infected with three pathogens. This study provided molecular evidence for the occurrence of Anaplasma spp., Ehrlichia spp., Rickettsia spp., and Brucella spp. circulating in pet dogs and their parasitic ticks in Junggar Basin, north-western China. These findings extend our knowledge of the tick-borne pathogens in pet dogs and their parasitic ticks in Central Asia; therefore, further research on these pathogens and their role in human and animal diseases is required.